A positive impact on the serum lipid profile and cytokines after the consumption of a plant sterol-enriched beverage with a milk fat globule membrane: a clinical study. Issue 10 (12th September 2018) - Alvarez-Sala, Andrea; Blanco-Morales, Virginia; Cilla, Antonio; Silvestre, Ramona Ángeles; Hernández-Álvarez, Elena; Granado-Lorencio, Fernando; Barberá, Reyes; Garcia-Llatas, Guadalupe
Abstract : Positive impact on serum lipids and cytokines after functional beverage's intake by postmenopausal women. Abstract : The hypocholesterolemic effect and the modification of serum biomarkers of a dietary plant sterol (PS) intake, cholesterol precursors and cytokines after the consumption of milk-based fruit beverages with a milk fat globule membrane were evaluated by a randomized, double-blind, crossover, multiple dose bioavailability study. Postmenopausal women ( n = 38) consumed daily 250 mL of a beverage with or without 2 g of PS added during 6 weeks in each of the study periods. With the intake of the PS-added beverage, significant decreases (mg dL −1 ) in serum total cholesterol (pre-treatment: 220.0 ± 27.8 vs. post-treatment: 212.9 ± 25.8; p < 0.05) and LDL-cholesterol (129.4 ± 28.5 vs. 121.7 ± 24.4; p < 0.05) were detected. The cholesterol precursor lathosterol (11.2%), markers of the dietary PS intake (campesterol 43.1% and β-sitosterol 32.5%), and anti-inflammatory IL-10 cytokine (22.5%) increased significantly, with a concomitant significant reduction in pro-inflammatory IL-1β (6.7%). No variations in HDL-cholesterol, other sterols (desmosterol and stigmasterol) or cytokines (IL-6, IL-8, IL-12p70 and TNF-α) were detected. These results indicated that this kind of PS-enriched milk-based fruit beverage is suitable during the period of clinical intervention, and its consumption may be an adequate way to improve PS functionality since a significant reduction in cholesterol levels has been observed. Therefore, the intake of this beverage could contribute to reduce the risk of cardiovascular disease also obtaining a beneficial effect on the serum inflammatory status in postmenopausal women.